ANALYSIS OF FACTORS AFFECTING ECONOMIC GROWTH IN INDONESIA FOR THE PERIOD 2013-2023 - Sutiman Sutiman; Dinda Thalia; Rachmawaty Rachmawaty (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to analyze the impact of exchange rates and inflation on Indonesia's economic growth from 2013 to 2023. Using a quantitative method, the research examines secondary data obtained from Bank Indonesia and the Central Statistics Agency (BPS). The dependent variable is economic growth, while the independent variables are exchange rates and inflation. Data analysis was conducted using classical assumption tests, multiple linear regression, and hypothesis testing through t-tests and F-tests. The findings reveal that exchange rates significantly affect economic growth, with a positive regression coefficient. This indicates that higher exchange rates contribute positively to economic growth by enhancing export competitiveness and influencing domestic economic activities. Conversely, inflation does not significantly impact economic growth, suggesting limited effects of inflation during the analyzed period. Simultaneously, exchange rates and inflation explain 83.5% of the variance in economic growth, demonstrating their combined influence. The study concludes that exchange rates are a crucial determinant of economic growth, while inflation requires further investigation for a comprehensive understanding. Policymakers should focus on maintaining stable exchange rates and controlling inflation to ensure sustainable economic development